2014
DOI: 10.1111/ans.12539
|View full text |Cite
|
Sign up to set email alerts
|

Caecal pneumatosis is not an absolute contraindication for endoluminal stenting in patients with acute malignant large bowel obstruction

Abstract: Caecal pneumatosis alone is not a reliable predictor of caecal viability in patients with acute malignant large bowel obstruction. Such a finding on CT scan should be correlated clinically before excluding the role of endoluminal stenting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Interestingly, Ozogul et al reported that of a total of 223 patients who had colon cancer, 26 patients presented with a colonic perforation proximal to the tumor (11.66%), representing the largest reported proportion of patients to be admitted with diastatic colonic perforation [1]. In a study of Ngu et al, 10 out of 60 (16.7%) patients admitted with acute malignant left colon obstruction were reported with CT evidence of cecal wall pneumatosis, a sign of possible imminent perforation, while only one was recognized with perforation through the tumor site [11]. In conclusion, diastatic colonic perforation occurs in approximately 0.7-1% of CRC patients, regarding the study by Ozogul et al as an outlier.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Ozogul et al reported that of a total of 223 patients who had colon cancer, 26 patients presented with a colonic perforation proximal to the tumor (11.66%), representing the largest reported proportion of patients to be admitted with diastatic colonic perforation [1]. In a study of Ngu et al, 10 out of 60 (16.7%) patients admitted with acute malignant left colon obstruction were reported with CT evidence of cecal wall pneumatosis, a sign of possible imminent perforation, while only one was recognized with perforation through the tumor site [11]. In conclusion, diastatic colonic perforation occurs in approximately 0.7-1% of CRC patients, regarding the study by Ozogul et al as an outlier.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the study analysed the correlation between caecal diameter in the axial plane and the risk of impending caecal perforation on abdominal X‐ray in 19 patients with distal large bowel obstruction and a control group of 100 patients with an artificial dilatation of the caecum and found that all patients with impending caecal perforation had a caecal diameter greater than 9 cm. This 9‐cm rule is often used in combination with other signs such as pericaecal fluid or caecal pneumatosis to raise the suspicion of impending caecal perforation .…”
Section: Discussionmentioning
confidence: 99%
“…Certain radiological features, such as poor enhancement of the bowel wall in the clinical context of metabolic acidosis with high lactate, should still alert the clinician to the possibility of an ischemic bowel, which can occur in cases of obstructive ileocolitis. However, the authors urge caution in interpreting all cases of pneumatosis intestinalis as definite evidence of an ischemic bowel as our earlier publication disputed this relationship [ 6 ]. To our knowledge, no prior study has conclusively proven that obstructive ileocolitis can be treated conservatively.…”
Section: Discussionmentioning
confidence: 99%